Opinion of Blind and Visually Impaired Patients and Caretakers on Braille Labeling on Medical Care Products Packaging in India - Khan, Zafar Parvez (Digital Repository of Theses, 2024)
Visual impairment has become a global issue, which is leading to various difficulties and has been significantly affecting BVI (Blind and Visually impaired) individuals life quality. As per literature review there are around more than 285 million people with visual impairment in the world and out of which around 90% live in developing side countries of the world. In India, currently there are around 12 million blind people which is making it a home to one third of the world’s blind and visually impaired population. This study was conducted involving 60 BVI (blind and visually impaired) individuals, 30 caretakers, and 42 pharmaceutical industry professionals to assess the need, viability, and implications of implementing Braille labeling on medical and healthcare packs. The primary aim was to validate the hypothesis that Braille labeling would enhance the independence of BVI patients in managing their healthcare need, reduction in accidental misuse, influence on purchase decision and its importance. In study, 42 out of 60 BVI mentioned a significant enhancement in independence, while 18 reported a somewhat enhanced experience; inclined towards enhancement of Independence. All 60 participants agreed that Braille labeling would significantly reduce accidental misuse of medicines; very strong indication of need to reduce accidental misuse of medicines. Furthermore, 58 respondents out of 60 believed that Braille labeling would positively influence purchase decisions even with marginal increase in cost, a strong input for industry. Regarding importance (need) of Braille labeling, 39 out of 60 BVI individuals deemed it very important, with 21 considering it important; indicates the need. The study also revealed through both BVI and caretakers that the primary challenge faced by BVI individuals was the identification and differentiation between similar packs. Moreover, caretakers also indicated that Braille labeling would increase independence (29 out of 30). Similarly, 19 out of 30 caretakers believed that Braille labeling would positively influence purchase decisions. Assessed the opinions of 42 industry professionals, major operational challenges identified included high-cost implications (by 69%), regulatory compliance (by 33.3%), production process modifications (by 45.2%), and challenge in availability of Braille experts (by 52.4%). Also, key technical challenges operations such as printing technology limitations (by 66.7%), quality control (by 45.2%), accuracy (by 50%), training and skill development of staff (by 64.3%) and space constraints on labels (by 54.8%) were also highlighted, no impact on design and aesthetics (by 47.6%), somewhat impact aesthetics and design (by 42.9 %). Overall, industry challenge is big & needs a model like public private partnership. All industry participants expressed lack of required level of communication regarding Braille labeling on medical pack in India with no existing policy. Overall, BVI populations indicates the dire need of such a tool like Braille labelling to gain independence while industry has its own challenges. A comprehensive discussion in country is needed to address both the sides, social inclusivity of BVI (Blind and visually impaired) individuals to access healthcare needs and in parallel address Industry challenges.